Comparison of Q-Coverage P-Connectivity Sensor Node Scheduling Heuristic Between Battery Powered WSN & Energy Harvesting WSN - Gupta, Sunita; Gupta, Sakar; Goyal, Dinesh (International Journal of Sensors Wireless Communications and Control, 2021)
A serious problem in Wireless Sensor Networks (WSNs) is to attain high-energy efficiency as battery powers a node, which has limited stored energy. They can not be suitably replaced or recharged. The appearance of renewable energy harvesting techniques and their combination with sensors give Energy Harvesting Wireless Sensor Networks (EH-WSNs). Therefore, the area shifts from energy preservation to the reliability of the network. For reliability, Coverage and Connectivity are important Quality of Service (QoS) parameters. Many sensor node scheduling heuristics have been developed in the past. Some of them focus on more than a single order of Coverage and Connectivity. If reliability is the main concern for a WSN, then there definitely is a need to incorporate Q-Coverage and P-Connectivity in WSN. The lifetime of a WSN decreases while considering Q-Coverage and P-Connectivity. After some time network dies and it is of no use. Therefore, there is a trade-off between the reliability and lifetime of a WSN. If EH-WSN is used, the lifetime of a WSN increases, as well as Q-Coverage and P-Connectivity QoS parameters can be used for achieving reliability. This paper proposes a sensor node scheduling heuristic for EH-WSN, considering Q-Coverage and P-Connectivity. A comparison of a Q-Coverage and PConnectivity sensor node scheduling heuristic, when used between battery powered WSN and EH-WSN, is done. The comparison shows that lifetime using EH-WSN is much greater as compared to battery powered WSN. This research is beneficial for real-time WSN applications where EH-WSN provides power regularly without any intervention.
Keywords: Pconnectivity